Miejsce metafor w badaniach nad komunikacją - Domaradzki, Mikołaj (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
The purpose of the present paper is to discuss several metaphorical conceptualizations of thephenomenon of communication from the perspective of cognitive linguistics. Apart from thepurely linguistic and philosophical issues, the article touches upon the questions that concern theprocess of teaching and learning a foreign language (especially the so called "radically differentone"). The thesis about our essentially metaphorical understanding of the phenomenon ofcommunication, widely acknowledged in cognitive linguistics, is supported by empirical datadrawn from Arabic and several Indo-European languages. Subsequently, the thesis is taken as apoint of departure for discussing such issues as the problem of cross-linguistic variation ofmetaphors and their biological motivation. The paper consists of three sections: the first oneexamines the metaphor of communication as transfer, the second considers the metaphor ofcommunication as enlightening, whereas the third presents some philosophical observations. Themost important conclusion that is drawn here has it that the potential universality of variousmetaphorical conceptualizations is a very useful heuristic and didactic tool, for the existence of acommon ground between languages that are genetically unrelated makes it possible not only toaccount for the ease with which certain elements of the target language can be translated into thesource language, but also to hypothesize about the general mechanisms that are responsible forunderstanding and acquiring the (radically) different target language. Needless to say, suchhypotheses are of paramount importance for the process of teaching and learning a foreign(especially radically different) language.